Qur’anic Learning Strategies for Improving Students’ Qur’anic Reading Ability at Pondok Pesantren Modern Darul Husna Langgapayung Labuhan Batu Selatan - Maria Patima Harahap (Jurnal Pendidikan Islam, 2026)
This study aims to describe Qur’anic learning strategies, portray the quality of students’ Qur’anic reading ability, and identify supporting and inhibiting factors in Qur’anic instruction at Pondok Pesantren Modern Darul Husna Langgapayung. A qualitative approach was employed, with data collected through interviews, observations, and documentation. Data analysis was conducted iteratively through data organization, selection, presentation of findings, and conclusion drawing, while data trustworthiness was strengthened through triangulation of techniques and sources. The findings indicate that Qur’anic instruction is implemented through a combination of strategies, namely cooperative learning (small groups of four to five students), the application of the Qira’ati method with immediate correction, habituation of Qur’anic reading before the start of lessons, and ability-based grouping (fluent and moderate). Based on Qur’anic reading assessments using indicators of fluency, smoothness, accuracy of makhraj, and tajwīd, out of 51 eighth-grade students, 31 students (60.8%) were classified as fluent and 20 students (39.2%) as moderate. Difficulties among the moderate group primarily involved the articulation of certain letters and the consistent application of tajwīd rules, particularly madd and ikhfā’. Supporting factors include students’ intrinsic motivation and sincere intention, teachers’ instructional innovation, and institutional facilities, while inhibiting factors encompass boredom, lack of motivation, and limited learning time. These findings underscore the importance of integrating technical instruction, habituation, cooperation, and differentiated learning services to achieve more equitable improvements in the quality of Qur’anic reading.